2021
DOI: 10.1097/med.0000000000000654
|View full text |Cite
|
Sign up to set email alerts
|

Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection and thyroid disease. An update

Abstract: Purpose of review Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection is associated with excess morbidity and mortality in patients with hypertension and diabetes but little is known about thyroid diseases. Thus, our goal was to review the literature with respect to: (i) Are patients with underlying hypo- or hyperthyroidism at increased risk of contracting SARS-CoV-2 infection? (ii) do underlying hypo- and hyperthyroidism impact the prognosis of SARS-CoV-2 infection? (iii) does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…The principal unmet needs identified were more remote access to thyroid specialists, psychological support and support for body weight control, as well as, explanations of the scientific evidence (relating to SARS‐COV‐2 and thyroid diseases) ‘in plain English’. The latter can be now documented and supported by scientific evidence, as specific studies of thyroid disease and COVID have emerged since the beginning of pandemic 8,9 . On the other hand, the reported rate of weight gain (53.1%) by responders indeed suggests a need for interventions that could have helped weight control during the pandemic, but also underscores the importance of weight‐control related measures that should be put in place for a potential expansion of the obesity pandemic.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The principal unmet needs identified were more remote access to thyroid specialists, psychological support and support for body weight control, as well as, explanations of the scientific evidence (relating to SARS‐COV‐2 and thyroid diseases) ‘in plain English’. The latter can be now documented and supported by scientific evidence, as specific studies of thyroid disease and COVID have emerged since the beginning of pandemic 8,9 . On the other hand, the reported rate of weight gain (53.1%) by responders indeed suggests a need for interventions that could have helped weight control during the pandemic, but also underscores the importance of weight‐control related measures that should be put in place for a potential expansion of the obesity pandemic.…”
Section: Discussionmentioning
confidence: 90%
“…Views expressed from professional thyroid organizations and the susceptibility of thyroid patients to SARS‐COV‐2 at the outset of the pandemic were generally reassuring, but some indicated a degree of caution in the absence of data and thyroid patients were encouraged to follow advice from governmental agencies 6,7 . Studies have since found that thyroid patients are indeed not at higher risk of contracting SARS‐COV‐2, and that their prognosis does not seem to differ from the background population when adjusted for preexisting other morbidities 8,9 . On the other hand, accumulating evidence suggests that thyroid dysfunction, especially thyrotoxicosis due to destructive thyroiditis, is present in a significant percentage of patients infected by SARS‐COV‐2 and correlates with the clinical severity of the illness 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The risk of COVID-19 in patients with thyroid diseases has been suggested [6,7]. First, angiotensin-converting enzyme 2 (ACE2) receptors are known to play a role in the entry of SARS-CoV-2 [8].…”
Section: Introductionmentioning
confidence: 99%
“…In a meta‐analysis investigating the effect of thyroid disease on the course of COVID‐19, they found a 148% increased risk of having a severe course of the disease, compared with people with no thyroid disease 41 . On the other hand, a study by Brix et al did not confirm an independent association between thyroid dysfunction and COVID‐19 42 . Hypothyroid patients have also been found to have a higher risk of developing a urinary tract infection after a Urodynamic Study 17,39 …”
Section: Discussionmentioning
confidence: 96%